QUALITY BY DESIGN-BASED OPTIMIZATION OF FORMULATION PARAMETERS TO DEVELOP NANOSTRUCTURED LIPID CARRIERS OF EZETIMIBE AND FENOFIBRATE FOR IMPROVING ITS BIOPHARMACEUTICAL PROPERTIES - BAKHATWAR, MOHAMMAD; SAINI, SUMANT; YADAV, D. PURNIMA; PRIYA, K. SWATHI; PRIYA, G. VEDA (International Journal of Applied Pharmaceutics, 2025)
Objective: In the current research work, Ezetimibe (EZT) and Fenofibrate (FBT), as they belong to BCS class II, have poor solubility and high permeability nature, which causes poor bioavailability and therapeutic failure. The drugs were formulated as nanoparticulate carrier systems to overcome the solubility problems associated with the drugs. So, the drugs were prepared as nanosuspension in the combination form using a polymer to enhance the drugs' bioavailability parameters. Methods: A novel technique was employed to prepare the formulation to improve the drugs' dissolution rate and bioavailability. In the current study, the antisolvent precipitation method was employed to formulate an EZT-FBT nanosuspension using a polymer, poloxamer 188. The best formulation was optimized by employing a design of experiments, i.e., a Plackett-Burman design, and an in vitro characterization of the best formulation was performed. Results: EZT and FBT nanosuspension formulation was successfully prepared by using poloxamer 188, methanol, and water as solvent and antisolvent. The optimized formulation FED-8 underwent characterization, which showed a particle size of 242.9 nm with high zeta potential, i.e.,-17 mV. 32 factorial design and Plackett-Burman design were employed for the optimization of the formulation parameters and the best formulation of nanosuspension. All the predetermined independent variables were found to affect the dependent variables from the resultant nanosuspension. All the studies, like saturation solubility, drug content, Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM), showed significant characteristic results. The kinetic studies of FED-8 were carried out, which showed 99.2% drug release in 2.5 h compared with the individual pure drugs. Conclusion: The study concludes that the Plackett-Burman design was effectively employed to identify formulating and processing key parameters affecting the quality of the EZT-FBT nanosuspension. This combinational approach enhanced the solubility and dissolution rate compared with pure drugs.